Theory and Practice of Conceptual Understanding in Physics Education: A Literature Review and Bibliometric Analysis of the Recent Decades - Wandi, Wandi; Mardianti, Fani; Suwarma, Irma Rahma; Liliawati, Winny (Kasuari: Physics Education Journal (KPEJ), 2023)
This paper aims to map the existing conceptual understanding literature to explore and classify current theory and practice in physics education. This paper systematically reviews research on conceptual understanding in the field of physics education from 2012 to 2023. The PRISMA framework for systematic literature was used, 278 research articles specific to physics education were identified through a structured keyword search in the SCOPUS database. The analysis revealed two important objectives in the conceptual understanding commonly used in physics education research. First, it relates to the distribution of conceptual understanding articles in terms of number per year, country, research discipline, and journal in which they are published. Second, revealing research collaboration between countries which is dominated by developed countries such as the United States, Germany, Chile, Croatia and Mexico. As for the future agenda, it is important to collaborate on research in developing countries.